Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3168/jds.2009-2179
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily milking effects in high-yielding Alpine dairy goats

Abstract: Two experiments were conducted to determine the milk loss of high-yielding Alpine goats resulting from once-daily milking (ODM) and its relationship to udder cisternal size. We investigated the effects of application of this management strategy on milk yield, composition, and technological parameters: lipolysis, fat globule size, and cheese yield. In a second experiment, we investigated the effect of repeated periods of ODM management during lactation. Goats at the beginning of both experiments were at 25 d in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
3
17
0
2
Order By: Relevance
“…In the present trial, we did not observe a time-dependent effect, as milk yield loss was found to be constant over the 5-week ODM period. This is consistent with the observations of Komara et al (2009), but not with our previous observations (Ben Chedly et al, 2011) or those of Salama et al (2003), in which milk yield loss was greater during the first weeks of ODM. This difference is likely attributable to the longer experimental period in those studies (15 and 24 weeks, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…In the present trial, we did not observe a time-dependent effect, as milk yield loss was found to be constant over the 5-week ODM period. This is consistent with the observations of Komara et al (2009), but not with our previous observations (Ben Chedly et al, 2011) or those of Salama et al (2003), in which milk yield loss was greater during the first weeks of ODM. This difference is likely attributable to the longer experimental period in those studies (15 and 24 weeks, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…For example, in the Murciano-Granadine breed, Salama et al (2003) found no differences in the SCC of tank milk by comparing one milking per day (1X) and two milkings a day (2X), although the SCN level was increased. On the other hand, Komara et al (2009), in two experiments realized with Alpine breed goats, found that only one of them, considering only multiparous goats, had an increase in counts going from 2X to 1X (179,800 and 400,300 cells mL -1 , respectively). These results could suggest that high yielding goats or specific breeds cannot be adapted to 1X (Komara et al, 2009).…”
Section: Milking Frequencymentioning
confidence: 96%
“…The goats thus received 800 g alfalfa, 1 kg energy concentrate and ad libitum hay and water, each day. The diet and the milking routines and equipment were previously described by Komara et al (2009). The goats in the TDM were milked at 0645 h and 1645 h, whereas those in ODM were milked at 1645 h.…”
Section: Animals and Experimental Designmentioning
confidence: 99%